Maria Montessori and the Mystery of Language Acquisition - Newman, Stephen; Archer, Nathan (Journal of Montessori Research, 2024)
Maria Montessori’s work remains popular and influential around the world. She provided fascinating descriptions of her observations of children’s learning. Yet at the heart of her work is a lacuna: the issue of how children learn their first language. For Montessori, it was a marvel, a miracle—but a mystery. We argue that the later philosophy of Ludwig Wittgenstein offers a way forward. With the clearer view offered by Wittgenstein’s reminders, we propose that Montessori’s work can be reevaluated to better understand Montessori’s contribution, child development and, in particular, how children acquire a first language.